Global Metabolic Profiling of Arabidopsis Polyamine Oxidase 4 (AtPAO4) Loss-of-Function Mutants Exhibiting Delayed Dark-Induced Senescence - Sequera-Mutiozabal, Miren I.; Erban, Alexander; Kopka, Joachim; Atanasov, Kostadin E.; Bastida, Jaume; Fotopoulos, Vasileios; Alcázar, Rubén; Tiburcio, Antonio F. (Frontiers in Plant Science, 2016)
Early and more recent studies have suggested that some polyamines (PAs), and particularly spermine (Spm), exhibit anti-senescence properties in plants. In this work, we have investigated the role of Arabidopsis Polyamine Oxidase 4 (PAO4), encoding a PA back-conversion oxidase, during dark-induced senescence. Two independent PAO4 (pao4-1 and pao4-2) loss-of-function mutants have been found that accumulate 10-fold higher Spm, and this associated with delayed entry into senescence under dark conditions. Mechanisms underlying pao4 delayed senescence have been studied using global metabolic profiling by GC-TOF/MS. pao4 mutants exhibit constitutively higher levels of important metabolites involved in redox regulation, central metabolism and signaling that support a priming status against oxidative stress. During senescence, interactions between PAs and oxidative, sugar and nitrogen metabolism have been detected that additively contribute to delayed entry into senescence. Our results indicate the occurrence of metabolic interactions between PAs, particularly Spm, with cell oxidative balance and transport/biosynthesis of amino acids as a strategy to cope with oxidative damage produced during senescence.